Cellulose utilization in forest litter and soil: identification of bacterial and fungal decomposers - Stursová, Martina; Zifčáková, Lucia; Leigh, Mary Beth; Burgess, Robert; Baldrian, Petr (FEMS microbiology ecology, 2012)
Organic matter decomposition in the globally widespread coniferous forests has an important role in the carbon cycle, and cellulose decomposition is especially important in this respect because cellulose is the most abundant polysaccharide in plant litter. Cellulose decomposition was 10 times faster in the fungi-dominated litter of Picea abies forest than in the bacteria-dominated soil. In the soil, the added (13)C-labelled cellulose was the main source of microbial respiration and was preferentially accumulated in the fungal biomass and cellulose induced fungal proliferation. In contrast, in the litter, bacterial biomass showed higher labelling after (13)C-cellulose addition and bacterial biomass increased. While 80% of the total community was represented by 104-106 bacterial and 33-59 fungal operational taxonomic units (OTUs), 80% of the cellulolytic communities of bacteria and fungi were only composed of 8-18 highly abundant OTUs. Both the total and (13)C-labelled communities differed substantially between the litter and soil. Cellulolytic bacteria in the acidic topsoil included Betaproteobacteria, Bacteroidetes and Acidobacteria, whereas these typically found in neutral soils were absent. Most fungal cellulose decomposers belonged to Ascomycota; cellulolytic Basidiomycota were mainly represented by the yeasts Trichosporon and Cryptococcus. Several bacteria and fungi demonstrated here to derive their carbon from cellulose were previously not recognized as cellulolytic.
Keywords: DNA fungální; DNA, Fungal; Carbon Isotopes; DNA bakterií; Picea; Trees; Fungi; Polymorphism, Restriction Fragment Length; Sequence Analysis, DNA; celulosa; stromy; houby; půda; biomasa; sekvenční analýza DNA; DNA, Bacterial; Cellulose; půdní mikrobiologie; geny hub; izotopy uhlíku; Genes, Fungal; Bacteria; Soil; polymorfismus délky restrikčních fragmentů; smrk; Biomass; Soil Microbiology